Bilingualism strategies in bilingual intercultural elementary schools: Implications towards the transformation of reading and writing practices - Manresa, Antonia (2020)
In September 2017, in Ecuador, the Ministry of Education supported a pilot project for mentors' training based on the methodological proposal of the Escuela Lectoras program of the Universidad Andina Simón Bolívar. This two-year project aimed to train approximately 50 pre-selected teachers to accompany classroom teachers in rural or peripheral urban areas to improve reading and writing in the first grades of Basic Education. Within the framework of this project, a research study was conducted on how Kichwa-speaking mentors use bilingualism and how this favors the teaching-learning process of reading and writing in bilingual contexts. The results of the study reveal three strategies for the use of bilingualism as part of the teaching-learning process of reading and writing: literal translation, communicative bilingualism, and linguistic exclusivity.